2016
DOI: 10.18632/oncotarget.8964
|View full text |Cite
|
Sign up to set email alerts
|

FXR agonists enhance the sensitivity of biliary tract cancer cells to cisplatin via SHP dependent inhibition of Bcl-xL expression

Abstract: Chemoresistance is common in patients with biliary tract cancer (BTC) including gallbladder cancer (GBC) and cholangiocarcinoma (CC). Therefore, it is necessary to identify effective chemotherapeutic agents for BTC. In the present study, we for the first time tested the effect of farnesoid X receptor (FXR) agonists GW4064 and CDCA (chenodeoxycholic acid) in combination with cisplatin (CDDP) on increasing the chemosensitivity in BTC. Our results show that co-treatment of CDDP with FXR agonists remarkably enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
6
14
0
Order By: Relevance
“…Our data suggested that activation of FXR by GW4064 acts synergistically with oxaliplatin to exert antitumor e cacy in vitro and in vivo. A previous study proved that FXR is hardly expressed and exhibits loss of function in CRC (41). Advanced stage patients, who are usually recommended to undergo chemotherapy, have better survival after using FXR agonists (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggested that activation of FXR by GW4064 acts synergistically with oxaliplatin to exert antitumor e cacy in vitro and in vivo. A previous study proved that FXR is hardly expressed and exhibits loss of function in CRC (41). Advanced stage patients, who are usually recommended to undergo chemotherapy, have better survival after using FXR agonists (9).…”
Section: Discussionmentioning
confidence: 99%
“…Among FXR target genes, SHP is thought to be pivotal in inhibiting tumor growth because it is a cell death receptor that targets mitochondria and induces apoptosis (44). FXR/SHP signaling induces dephosphorylation of STAT3 and inhibits expression of its target Bcl-xL (41). In addition, SHP can translocate to mitochondria, bind to Bcl-2, and cause Cyto C release to the cytoplasm (45).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial apoptosis, which is induced by DNA damage and cellular stress, is inhibited by the anti-apoptotic Bcl-2 protein Bcl-xL. Bcl-xL is thought to decrease the sensitization of cancer cells to CDDP by stabilizing the Δ Ψ m and preventing the release of apoptosis-inducing molecules such as cytochrome c, Smac and AIF [ 28 ]. In addition, TG2, a Bcl-2 homology 3 (BH3) enzyme involved in protein cross-linking and overexpressed in cancer, has anti-apoptotic effects in cancer cells and plays a key role in the response to CDDP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated STAT3 modulates the function of numerous substrates, including cell proliferation and apoptosis (40). There is ample evidence to indicate that the STAT3 pathway is uncontrolled in GBC (28,41). It was found in our study that LKB1 plays a negative role in GBC cells and inhibits GBC cell growth and metastasis by inactivating STAT3 signaling.…”
Section: Discussionmentioning
confidence: 52%